AN IMPLEMENTATION AND COMPARATIVE ANALYSIS OF FUSION TECHNIQUES ON MEDICAL IMAGES - Joshi, M.R; Helonde, Mr. Roshan P (IJRDO -Journal of Computer Science Engineering, 2015)
Image fusion is the techniqueof merging several images from multi-modalsources with respective complementaryinformation to form a new image, whichcarries all the common as well ascomplementary features of individual images.With the recent rapid developments in thedomain of imaging technologies, multisensorysystems have become a reality in wide fieldssuch as remote sensing, medical imaging,machine vision and the military applications.Image fusion provides an effective way ofreducing this increasing volume ofinformation by extracting all the usefulinformation from the source images. Imagefusion creates new images that are moresuitable for the purposes of human/machineperception, and for further image-processingtasks such as segmentation, object detectionor target recognition in applications such asremote sensing and medical imaging. Theoverall objective is to improve the results bycombining DWT with PCA and non-linearenhancement. The proposed algorithm isdesigned and implemented in MATLABusing image processing toolbox. Thecomparison has shown that the proposedalgorithm provides a significant improvementover the existing fusion techniques.